PKM PETANI PISANG DI KAMPAR - Syafriani; Afiah; Nia Aprilla (Universitas Pahlawan Tuanku Tambusai, 2022)
Kampar Regency is one of the banana producers in Riau Province. As a producer of very broad bananas, many types are planted, such as: plantain, stone, bantan, sticks and so on. Bananas are very easy to get at a cheaper price, so they have the potential to develop activities into various variations and have a high selling value. This banana is very useful, banana is a healthy and delicious type that contains fiber, antioxidants and also contains lots of Vitamin C, Vitamin B6, carbohydrates and protein which are good for consumption for anyone. Bananas are an important source of fiber which helps the digestive system and is good for dieting. The purpose of this activity is to assist farmers in increasing the purchase of bananas produced by processing bananas into healthy, tasty, and attractive products for consumers to sell. Processed products such as banana satay, banana sigho and banana sanok. Banana processing is expected to improve the economy of banana farmers because so far bananas are only sold cheaply to collectors or traders at very low prices and get little profit from their harvests. Constraints faced by farmers are the use of science and technology in terms of banana production by using a blender, the purchase price of banana farmers is not proportional to the profits obtained because collectors and actors provide low prices to farmers, low motivation in banana processing. Activities that will be carried out in this Community Partnership Program include several development efforts, namely: 1. Use of science and technology in terms of banana production, which aims to make it easier for farmers to start, 2. motivate banana farmers to become entrepreneurs, 3. Training / practice of making products from bananas because there are so many products that can be made from bananas themselves. The product variants made are banana satay, sigho banana, sanok banana, 4. Packing / packaging the product until it is ready for sale, 5. Sales strategy with bananas to collectors or directly to the traditional market in Kampar district. And processed products from bananas will be sold to stalls, or opening stalls, on the internet. Keywords: Banana satay, banana sanok, and banana sigho